Protecting our WATERS: A 5E lesson sequence derived from a National Science Foundation-funded middle school watershed sustainability curriculum. (3rd April 2022) - Krauss, Zachary; Kline, David; Marcum-Dietrich, Nanette I; Stunkard, Cynthia; Kerlin, Steve; Staudt, Carolyn
Abstract: Oftentimes, due to the involute nature of the issues involved, society leaves it up to the experts to tackle the environmental problems currently facing society. However, a more wholistic approach is needed to address these environmental issues in the timely fashion necessary. With a reductionist treatment of sustainable development issues, the concepts involved can be broken down to a level accessible by the public. WATERS: Watershed Awareness using Technology and Environmental Research for Sustainability, is a 10-lesson watershed sustainability curriculum directed at middle school students. Using online, classroom, and field-based components, WATERS seeks to make watershed sustainability and conservation an accessible topic for students around the United States, hoping to create a generation of Environmentally Literate citizens who have the knowledge and desire to tackle the pressing issues facing the natural world around them. While the complete WATERS curriculum consists of ten lessons, this article will describe a 5E sequence that consists of four of the ten lessons.